Operating Guidelines for the AMAP Working Group. - Arctic Monitoring and Assessment Programme (AMAP) (Arctic Monitoring and Assessment Programme (AMAP), 2014)
Operating guidelines of the Arctic Council working group Arctic Monitoring and Assessment Programme (AmAP), submitted to the Senior Arctic Officials meeting in Yellowknife, Canada, October 22-23 2014. NOTE: The operating guidelines as presented in this document have not been finally adopted, and should therefore not be viewed as the final version of the operating guidelines.